FEEDING HABITS AND GONAD MATURITY LEVELS OF MACKEREL (Scomberomorus commerson) LANDED AT THE RENGAS RIVER COASTAL FISHING PORT - Stefani, Karyn Irene Teresa; Munir, Ahmad Mulyadi Sirodjul; Anzani, Yunita Magrima (Universitas Mataram, 2025)
Coastal Fishing Port (PPP) is a landing place for fish caught by fishermen, including pelagic fish. The production of mackerel catches in the Rengas River PPP has decreased from 2012 to 2021. Due to the decline in mackerel fish catch production, research related to the reproduction of mackerel is needed. The aim of this research is to analyze eating habits, TKG, IKG, and IHS. The fish sampling method was carried out using the purposive sampling method. Sampling of 20 mackerel fish is carried out once a month. Mackerel fish are carnivorous fish, which can be seen from the type of mackerel mouth, namely terminal, the shape of the mackerel fish's teeth, which are canine-like, and the fish's gill filter, which is large and has few filaments. The average length of a mackerel fish's intestines is 0.59 cm of its body length, so it is classified as a carnivorous fish. The level of maturity of male gonads was highest in TKG IV and female gonads in TKG II, the average IKG of male gonads was 0.96%, and female gonads 1.13%. The liver of female mackerel fish (Scomberomorus commerson) experiences changes in weight as measured by the Hepatosomatic Index along with increasing egg growth based on TKG.